Tasawuf dalam Layar Wayang: Mengupas Makna Spiritual Dewa Ruci - Apriliani, Wella Ayu (Jurnal Riset Agama, 2024)
This research project aims to analyze the concept of tasawwuf, as presented in the Dewa Ruci puppet story, as a representation of the spiritual journey towards insan kamil (perfect human being). This research employs a qualitative approach with a descriptive-analytical methodology. This research focuses on the concept of Sufism as its formal object, while the material object is the story of Wayang Dewa Ruci, particularly Bima's journey to achieve spiritual enlightenment. This research examines the interconnection between the tenets of Sufism and the narrative structure of wayang stories within the context of Javanese spiritual beliefs. The results demonstrate that the Dewa Ruci narrative reflects the stages of Sufism, namely takhalli (self-purification), tahalli (cultivation of good qualities), and tajalli (inner enlightenment). These stages are also related to the concept of manunggaling kawula Gusti (unity of servant with God) in Javanese mysticism. This study concludes that Wayang Dewa Ruci not only conveys moral and cultural messages, but also contains Sufism teachings that are relevant in the context of kejawen spirituality. It is recommended that further study of Sufism in local culture be undertaken, and that educational and cultural institutions integrate spiritual values in education and artistic preservation.